2017
DOI: 10.4103/1008-682x.181816
|View full text |Cite
|
Sign up to set email alerts
|

Chloride channels are involved in sperm motility and are downregulated in spermatozoa from patients with asthenozoospermia

Abstract: Human spermatozoa encounter an osmotic decrease from 330 to 290 mOsm l−1 when passing through the female reproductive tract. We aimed to evaluate the role of chloride channels in volume regulation and sperm motility from patients with asthenozoospermia. Spermatozoa were purified using Percoll density gradients. Sperm volume was measured as the forward scatter signal using flow cytometry. Sperm motility was analyzed using computer-aided sperm analysis (CASA). When transferred from an isotonic solution (330 mOsm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In spite of this approved identification, published evidence for classifying the samples into normospermic, teratospermic, oligospermic and asthenospermic as listed in WHO (2010) criteria was presented herein. Ji et al (2017) and Liu et al (2017) identified the different infertility cases according to sperm count and motility. Asthenospermia was identified by reduction in sperm motility lower than 40% motile sperms.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this approved identification, published evidence for classifying the samples into normospermic, teratospermic, oligospermic and asthenospermic as listed in WHO (2010) criteria was presented herein. Ji et al (2017) and Liu et al (2017) identified the different infertility cases according to sperm count and motility. Asthenospermia was identified by reduction in sperm motility lower than 40% motile sperms.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of sperm membrane integrity alters the diffusion of ions across the membrane and dysregulates the function of ion pumps and channels, especially as those ion channels that are regulated by PUFAs (reviewed in [90]). Although there is currently limited direct evidence linking sperm membrane integrity and ion channel function, the peroxidation of lipids and the downregulation of some ion channels in low-motility spermatozoa has been documented [83,[91][92][93][94]. In this context, Baker et al [22] reported two sperm ion channels, voltage-dependent anion-selective channel protein 2 (VDAC2) and sodium/potassium-transporting ATPase subunit alpha-4 (ATP1A4) that are susceptible to the formation of potentially deleterious adducts with 4HNE.…”
Section: Compromised Sperm Membrane Integritymentioning
confidence: 99%
“…In view of the complexity of the regulatory pathways in sperm motility, it appears that any abnormalities of these pathways could contribute to impaired sperm motility. For example, mutation of a sperm-specific subunit of PKA does not affect the process of spermatogenesis, but impairs the capability of forward motility in mature sperm [6]; aberrated expression of the ion channel, such as with the voltage-dependent anion channel and chloride channels, could result in poor sperm motility and consequently asthenozoospermia [7,8].…”
Section: Introductionmentioning
confidence: 99%